The rabbit, the fox, and the wolf - Sara. (New York : Orchard Books, 1990)
After a rabbit, chased by a fox, is saved by a wolf, the rabbit and the wolf become friends.
Translation of: Dans la gueule du loup.
School Library Journal
K-3
Keywords: Rabbits -- Fiction; Wolves -- Fiction; Friendship -- Fiction; Stories without words; Rabbits -- Fiction; Wolves -- Fiction; Friendship -- Fiction; Stories without words